Semantic Distribution and Collocation: Corpora Study of Synonyms See and Watch - Adibah Adibah; Beta Rida Pasaribu; Siti Sumarti (Universitas Muhammadiyah Mataram, 2026)
@font-face font-family:SimSun; panose-1:2 1 6 0 3 1 1 1 1 1; mso-font-alt:宋体; mso-font-charset:134; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:3 680460288 22 0 262145 0;@font-face font-family:Century; panose-1:2 4 6 4 5 5 5 2 3 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:647 0 0 0 159 0;@font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-536870145 1107305727 0 0 415 0;@font-face font-family:"\@SimSun"; panose-1:2 1 6 0 3 1 1 1 1 1; mso-font-charset:134; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:3 680460288 22 0 262145 0;p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman",serif; mso-fareast-font-family:"Times New Roman";.MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; mso-fareast-font-family:SimSun; mso-ansi-language:EN-US; mso-fareast-language:EN-US;div.WordSection1 page:WordSection1;Synonymy has long been a source of confusion for English language learners, particularly in distinguishing verbs that share similar meanings, such as see and watch. This study aims to use corpora to investigate the distinctions between these two synonymous verbs in terms of collocations and semantic distributions. Data were drawn from two written learner corpora: LOCNESS (The Louvain Corpus of Native English Essays), comprising 176 essays (149,574 words) written by American English learners, and GLC (Gachon Learner Corpus), comprising 212 essays (25,247 words) written by intermediate Korean English learners. Analysis was conducted using AntConc 3.5.9, applying loglikelihood statistics within a 4L-4R span, and cross-verified through the Collins Online Dictionary and Oxford Learner's Dictionary. The findings revealed that see was used considerably more often than watch in both corpora, consistent with its broader semantic range (14 senses in Collins and 18 in OLD, compared to 5 senses for watch). Regarding semantic distribution, Korean learners tended to favor literal, transparent senses of both verbs, while American learners employed a wider range of senses, including more opaque meanings of see. These findings carry important pedagogical implications, emphasizing the need to teach synonyms across their literal to the most opaque senses, and highlighting the value of corpus-based approaches in vocabulary instruction.